Optimization of Mathematics Learning with Problem Based Learning and 3N (Niteni, Nirokke, Nambahi) to improve mathematical problem solving skills - Wijayanti, Astuti; Widodo, Sri Adi; Pusporini, Widowati; Wijayanti, Nisa; Irfan, Muhamamd; Trisniawati, T (Universitas Sarjanawiyata Tamansiswa, 2022)
Learning mathematics is considered a difficult subject for students. Learning difficulties experienced by students often have an impact on the lack of awareness of the importance of mathematics in students' daily life. Optimization of learning mathematics with problem-based learning can be applied using the 3N teachings of Tamansiswa concepts, namely Niteni, Nirokke, Nambahi. This research is qualitative in the form of a literature review. This article describes how teachers can optimize PBL with Tamansiswa teachings in learning mathematics so that students become enjoy, more effortless, and responsive in applying mathematical concepts in daily life.